THE IMPACT OF ECOSYSTEM SERVICES ON THE INTENSIFICATION OF AGRICULTURAL PRODUCTION (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The article analyzes the situation in the field of ecosystem services of Volyn region and considers the role of beekeeping in increasing the potential productivity of agricultural production. Achievements, problems and tasks of ecosystem services at the current level of development of agricultural production are revealed. It has been proved that pollination of entomophytic crops by honey bees is the cheapest, most effective and ecologically clean factor of growth of crop production. The priorities of strategies and action plans for socially, economically and ecologically balanced development of rural areas, aimed at creating a full living environment for modern and future generations based on the rational use of resources. It is noted that the real opportunities of Ukraine's agriculture, in particular crop production and beekeeping, to increase economic efficiency and competitiveness of industries should consist of the most important factors that must be realized through the development of regional programs for their development. It is proved that Volyn region has a high potential in this area, which in terms of improving the efficiency of the domestic agro-industrial complex should be used to the maximum. Problems that do not allow to make full use of opportunities and achieve maximum economic efficiency in these areas are considered. The article draws attention to the fact that these problems are relevant not only for agricultural production, but also for sustainable development of rural areas.
Keywords: rural areas, economic efficiency, ecosystem services, beekeeping, pollination, crop production, yield.